How Terror Attacks Shape Political Agendas on Multiculturalism in France - Elena Cossu; Caterina Froio (Politics and Governance, 2025)
Terror attacks do more than take lives, they reshape the boundaries of political discourse. This article examines how terror attacks in France (2014–2021) influenced political agendas on multiculturalism by analyzing 143,870 tweets from major political parties. Drawing on data from the AUTHLIB project, we apply multilingual RoBERTa and DistilBERT models for natural language inference and sentiment analysis. While evidence of salience contagion is limited, our findings reveal position contagion: mainstream parties adopted increasingly negative rhetoric on cultural diversity and especially Islam in the aftermath of attacks, echoing far‐right narratives. In contrast, the Front National (renamed Rassemblement National in 2018) consistently maintained its negative framing. This dual dynamic—mainstream parties shifting rightward while far‐right rhetoric remains constant—contributes to the normalization of illiberal positions in French politics, where civic values, particularly laïcité, are deployed to justify cultural and religious exclusion. Methodologically, the article introduces an innovative approach for tracking party positions over time using social media data and natural language processing. Beyond the French case, the study underscores a broader paradox: liberal democracies, in seeking to defend their foundational values, may increasingly adopt illiberal discourse that undermines the very principles they aim to protect.